Muslim Minorities in the West - Ghulam M. Haniff (International Institute of Islamic Thought, 1997)
In this superb compilation of essays, fourteen scholars provide a timely assessment of the expanding Muslim communities in ten western countries, carefully describing their growth and development, sometimes in minute historical detail, as they are increasingly scrutinized under the global spotlight for a variety of complex reasons. Produced as a serious work of research, this volume represents one of the first attempts to examine systematically the status and nature of Muslim collective life in the western diaspora as seen from the theoretical perspective of the majority-minority relationship. It developed out of a conference convened to consider the condition of the Islamic minorities worldwide. After the conference, selected papers were transformed into chapters written specifically for inclusion in this book. Through fourteen rich and original articles, this book explores a plethora of problems confronting Muslims, both the recent immigrant arrivals in Europe, Australia, and North America as well as the indigenous followers of Islam in the Balkans, living within communal collectivities of the Western world. It considers “how Muslim minorities fulfill their religious rites and obligations, engage in social and community life and educate their young.” It examines “the sacrifices Muslims have to make and the price they have to pay to maintain or to acquire a Muslim identity.” With two essays each on Australia, Canada, and the United States, and Britain, the English-speaking world, gets the most attention. But the more obscure cases of Bosnia and Bulgaria, both the terra incognita of the Islamic world until the recent tragedy, are analyzed thoroughly by their native sons, Smail Balic and Kemal Karpat. Despite a diversity of academic orientation, the essays are all highly stimulating, and the quality of the contributions are all equally superior. The overarching dilemma, identified by the authors as the culprit responsible for the Muslims’ difficulties, is the demonization of Islam and the Islamic people in the western worldview. As a powerful psychological force on western thinking, this mindset has brought about the victimization of Muslims and has led to their wholesale discrimination, indeed, to their rejection as the undesirable “other.” The first two chapters of the book, directly relevant to this concern, delve into the agony of the Muslims of Bosnia; despite their ethnic and racial compatibility with the Slavic majority notwithstanding, they have undergone one of the most gruesome incidents of calculated mass murder and brutality in recent European history. In spite of Bosnia’s “open-minded, liberal and tolerant” p. 23) nature, it has not been spared “a ruthless genocide” p. 24), perhaps because Islam rejects the underlying racist premise of the nation-state and is therefore seen as a subversive force. Commensurately, history seems to be repeating itself in Europe. Almost five hundred years after the obliteration of Islam from Spain, Khalid Duran points out that Bosnia, “truly a cosmopolitan society” p. 30), is being turned into another Andalusia ...